Discovery of Novel Natural Products with Therapeutic Potential - Gullo, Vincent P. (Newnes, 2013)
Although science has discovered effective drugs for many of the diseases that afflict mankind, many human health problems remain untreatable. The search for novel therapeutic agents is always ongoing. This book will describe some of the diverse sources of natural products, such as terrestrial and marine environments; and will review how research has increased knowledge of biological systems and human disease, leading to the design of targeted asssays, amenable to high volume screening.